2020
DOI: 10.1186/s40657-020-00217-6
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of avifaunal diversity along the elevational gradient of Mardi Himal in Annapurna Conservation Area, Central Nepal

Abstract: Background: Patterns of biological diversity and richness can vary along the elevational gradients among mountain systems making it difficult to conclude the general pattern. The drivers of such pattern are also poorly known in the southern flank of the Himalaya due to limited studies. Therefore, we assessed the species richness, seasonal patterns and drivers of avian diversity along an elevational gradient on Mardi Himal trekking trail, a newly open tourist route in Annapurna Conservation Area of the central … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
30
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 90 publications
4
30
2
Order By: Relevance
“…In general, species richness has been reported to follow one of the four main diversity patterns: decreasing with elevation, low plateau, low plateau with a midelevation peak, and mid-elevation peaks. Of these, midelevation peaks are the mostly observed patterns among vertebrates (Colwell & Lees 2000;Bertuzzo et al 2016;Chen et al 2017;Pandey et al 2020). These patterns can be explained by drivers that can be both spatial (area, mid domain effect) and environmental (temperature, precipitation, productivity, and habitat heterogeneity) (Colwell et al 2004;Wu et al 2013;Chen et al 2017Chen et al , 2020Pandey et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, species richness has been reported to follow one of the four main diversity patterns: decreasing with elevation, low plateau, low plateau with a midelevation peak, and mid-elevation peaks. Of these, midelevation peaks are the mostly observed patterns among vertebrates (Colwell & Lees 2000;Bertuzzo et al 2016;Chen et al 2017;Pandey et al 2020). These patterns can be explained by drivers that can be both spatial (area, mid domain effect) and environmental (temperature, precipitation, productivity, and habitat heterogeneity) (Colwell et al 2004;Wu et al 2013;Chen et al 2017Chen et al , 2020Pandey et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Of these, midelevation peaks are the mostly observed patterns among vertebrates (Colwell & Lees 2000;Bertuzzo et al 2016;Chen et al 2017;Pandey et al 2020). These patterns can be explained by drivers that can be both spatial (area, mid domain effect) and environmental (temperature, precipitation, productivity, and habitat heterogeneity) (Colwell et al 2004;Wu et al 2013;Chen et al 2017Chen et al , 2020Pandey et al 2020). Numerous hypotheses have been proposed to explain relationships between species richness and altitude, such as species-area relationships, mid-domain effects, climate-richness relationships, and productivity-richness relationships (Rahbek 1995;Grytnes & Vetaas 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Spatiotemporal distribution of some key environmental resources governs abundance of bird species (McCain 2009). Therefore, studies have attempted to study factors that affect bird abundance and distribution at spatial and temporal scales (He et al 2019;Pandey et al 2020). Studies have shown association of particular bird species to the specific habitat (Brawn et al 2001;Seymour and Simmons 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Annapurna Conservation Area (ACA) is one of the Important Bird and Biodiversity Areas (IBAs) and a global hotspot of bird diversity (BCN 2011;Pandey et al 2020). It is one of the largest protected areas of Nepal covering an area of 7629 square kilometers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation